Quality dominant logic in big data analytics and firm performance. Issue 3 (27th June 2019) - Fosso Wamba, Samuel; Akter, Shahriar; de Bourmont, Marc
Abstract : Purpose: Big data analytics (BDA) gets all the attention these days, but as important—and perhaps even more important—is big data analytics quality (BDAQ). Although many companies realize a full return from BDA, others clearly struggle. It appears that quality dynamics and their holistic impact on firm performance are unresolved in data economy. The purpose of this paper is to draw on the resource-based view and information systems quality to develop a BDAQ model and measure its impact on firm performance. Design/methodology/approach: The study uses an online survey to collect data from 150 panel members in France from a leading market research firm. The participants in the study were business analysts and IT managers with analytics experience. Findings: The study confirms that perceived technology, talent and information quality are significant determinants of BDAQ. It also identifies that alignment between analytics quality and firm strategy moderates the relationship between BDAQ and firm performance. Practical implications: The findings inform practitioners that BDAQ is a hierarchical, multi-dimensional and context-specific model. Originality/value: The study advances theoretical understanding of the relationship between BDAQ and firm performance under the influence of firm strategy alignment.